Cognitive-motor integration deficits in young adult athletes following concussion - Brown, J. A.; Dalecki, M.; Hughes, C.; Macpherson, A. K.; Sergio, L. E. (BMC Sports Science, Medicine and Rehabilitation, 2015)
Background